E-module as an emergency-innovated learning source during the Covid-19 outbreak - Purnamasari, Niken; Siswanto, Siswanto; Malik, Shazia (Research and Social Study Institute, 2020)
The COVID-19 pandemic has hugely changed various human activities. This